Altered diversity and composition of gut microbiota in Wilson's disease - Xiangsheng Cai (Nature Portfolio, 2020)
Abstract Wilson’s disease (WD) is an autosomal recessive inherited disorder of chronic copper toxicosis with high mortality and disability. Recent evidence suggests a correlation between dysbiosis in gut microbiome and multiple diseases such as genetic and metabolic disease. However, the impact of intestinal microbiota polymorphism in WD have not been fully elaborated and need to be explore for seeking some microbiota benefit for WD patients. In this study, the 16S rRNA sequencing was performed on fecal samples from 14 patients with WD and was compared to the results from 16 healthy individuals. The diversity and composition of the gut microbiome in the WD group were significantly lower than those in healthy individuals. The WD group presented unique richness of Gemellaceae, Pseudomonadaceae and Spirochaetaceae at family level, which were hardly detected in healthy controls. The WD group had a markedly lower abundance of Actinobacteria, Firmicutes and Verrucomicrobia, and a higher abundance of Bacteroidetes, Proteobacteria, Cyanobacteria and Fusobacteria than that in healthy individuals. The Firmicutes to Bacteroidetes ratio in the WD group was significantly lower than that of healthy control. In addition, the functional profile of the gut microbiome from WD patients showed a lower abundance of bacterial groups involved in the host immune and metabolism associated systems pathways such as transcription factors and ABC-type transporters, compared to healthy individuals. These results implied dysbiosis of gut microbiota may be influenced by the host metabolic disorders of WD, which may provide a new understanding of the pathogenesis and new possible therapeutic targets for WD.